2017
DOI: 10.1051/0004-6361/201630004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterisation of the globular cluster NGC 5634 associated to the Sagittarius dwarf spheroidal galaxy

Abstract: As part of our on-going project on the homogeneous chemical characterisation of multiple stellar populations in globular clusters (GCs), we studied NGC 5634, associated to the Sagittarius dwarf spheroidal galaxy, using high-resolution spectroscopy of red giant stars collected with VLT/FLAMES. We present here the radial velocity distribution of the 45 observed stars, 43 of which are cluster members, the detailed chemical abundance of 22 species for the seven stars observed with UVES-FLAMES, and the abundance of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…Kayser et al 2008;Smolinsky et al 2011), O and Na, and Mg and Al (see e.g. Carretta et al 2009a,b;Bragaglia et al 2015;Carretta et al 2017 and references therein for our FLAMES survey of more than 25 MW GCs). Photometrically, light element variations manifest in colour-magnitude diagrams (CMD) as sequence broadening and splitting (e.g.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Kayser et al 2008;Smolinsky et al 2011), O and Na, and Mg and Al (see e.g. Carretta et al 2009a,b;Bragaglia et al 2015;Carretta et al 2017 and references therein for our FLAMES survey of more than 25 MW GCs). Photometrically, light element variations manifest in colour-magnitude diagrams (CMD) as sequence broadening and splitting (e.g.…”
Section: Introductionmentioning
confidence: 88%
“…To increase the sample studied with high-resolution spectroscopy, we obtained data for a few old and massive open clusters (OCs; i.e. Berkeley 39, NGC 6791: Bragaglia et al 2012Bragaglia et al , 2014 and low-mass GCs, which are also connected with the Sgr dSph (Terzan 8, NGC 6139, and NGC 5634;Carretta et al 2014a;Bragaglia et al 2015;Carretta et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Two other clusters, NGC 5024 and NGC 5053, have at some point been linked to Sagittarius, although recent proper motion measurements have demonstrated this association is unlikely (see Law & Majewski 2010;Sohn et al 2018;Gaia Collaboration, Helmi et al 2018). Also NGC 5634 has been related to Sagittarius (Law & Majewski 2010;Carretta et al 2017) based on its position and radial velocity. However, the proper motion of the system measured by Gaia Collaboration, Helmi et al (2018) is very different from the prediction by for example, the Law & Majewski (2010) model of the Sagittarius streams.…”
Section: Association With Globular Clustersmentioning
confidence: 99%
“…NGC 5634 was first proposed to be associated to an ancient wrap of the stream by Bellazzini et al (2002) and Bellazzini et al (2003a). Later Law & Majewski (2010b) and Carretta et al (2017) confirmed it as a good candidate. In the metalpoor regime the abundance patterns of the Milky Way and of Sgr dSphs are very similar.…”
Section: Ngc 5634mentioning
confidence: 99%